CD146 is required for VEGF-C-induced lymphatic sprouting during lymphangiogenesis - Huiwen Yan (Nature Portfolio, 2017)
Abstract VEGF-C is essential for lymphangiogenesis during development and tumor progression. VEGFR-3 is the well-known cognate receptor of VEGF-C to regulate lymphatic migration and proliferation, but the receptor of VEGF-C in regulating lymphatic sprouting, the initiating step of lymphangiogenesis, still remains elusive. Here we use both in vitro and in vivo methods to demonstrate CD146 as a receptor of VEGF-C to regulate lymphangiogenesis, especially at the sprouting step. Mechanistically, CD146 selectively activates the downstream p38 kinase, upon VEGF-C stimulation, to regulate lymphatic sprouting. Moreover, CD146 can also activate ERK to mediate VEGF-C regulation of the subsequent proliferation and migration of lymphatic endothelial cells. In zebrafish embryos, knockdown or dysfunction of CD146 results in similar developmental defects in lymphatic sprouting, capillary network, parachordal lymphangioblast (PL), and thoracic duct (TD) similar to down-regulation of VEGF-C. Altogether, our data reveals a critical role of CD146 to mediate VEGF-C signaling pathway in lymphangiogenesis.